Tracked Changes. Aerospace series. Screw, pan head, offset cruciform recess, close tolerance normal shank, short thread, in alloy steel, cadmium plated. Classification: 900 MPa (at ambient temperature)/235 °C. (15th March 2023) - British Standards Institution,
No abstract available